Reforma Alutsista dan Sumber Daya Alam: Menjawab Tantangan Hukum Internasional dan Perdamaian Dunia - Fikri, Wildan Azkal; Aisy, Rohadhatul (UI Scholars Hub, 2026)
This study departs from the paradox of the failure to achieve world peace despite the existence of an established international legal regime. It addresses three main objectives: (1) identifying the key factors that undermine world peace; (2) analyzing the failure factors of international law to realize global peace; and (3) formulating a responsive international legal architecture to future peace agendas. The study employs a critical descriptive method with a socio-legal (non-doctrinal) approach, drawing on the analytical frameworks of neorealism, great powers oligarchy, and Third World Approaches to International Law (TWAIL). The qualitative analysis is conducted by examining power relations, the distribution of natural resources, and the configuration of global military capabilities. The findings reveal that the anarchic structure of the international system constitutes the primary driver of global conflicts as reflected in World War I and II. Furthermore, the dominance of the Permanent Five (P-5) has produced a great powers oligarchy that distorts the principles of international law and obstructs world peace. This study argues that reforming the distribution of military capabilities and access to natural resources is a crucial prerequisite for non-P-5 states to reconstruct international law. Accordingly, a redesign of the architecture of international law is needed to make it more just, inclusive, and balanced global distribution of power orientation as a foundation for sustainable world peace.